Der Einzugsbereich einer Fremdenverkehrsgemeinde (Beispiel Boppard): Erfassung mit Hilfe von Stichproben: Fehlerquellen und Kontrollmöglichkeiten - Hahn, Helmut (ERDKUNDE, 1981)
The difficulty of locating the places of origin of tourists, especially of day visitors, but also of overnight guests, is the cause of the great difficulty of demarcating the catchment areas of municipalities engaged in tourism. It is for that reason that the opportunity has been taken for some time of noting down the registration numbers of parked vehicles as a means of locating the catchment area with relatively little effort. The example of such data collections in Boppard on the Middle Rhine serves to prove that isolated collections or a few counts on so-called representative or normal days do not provide a sufficient base for the definition of the catchment area because of fluctuations resulting from the most diverse external circumstances and behaviour patterns. Only numerous counts paying the best balanced attention possible to the rhythm of the week, as well as to that of the year, to local peculiarities and so on are able to minimise the sources of error. Since individual groups of visitors use cars as the means of arrival in differing proportions, and day visitors cover distances different from those of overnight guests the noting-down of registration numbers needs to be supplemented by separate questioning of each group of visitors. These will of course not only have to attain a sufficient volume of sample surveys but also to take into account the criteria mentioned above. In the case of Boppard there emerges a clearly definable, bipartite nucleus, the southern part of which is the catchment area of day visitors, while the northern part caters for day and overnight guests. It is surrounded by a marginal zone in which overnight guests again predominate in the north, and day visitors in the south. Only the marrying of the methods of investigation justifies hopes for a realistic result.